2022
DOI: 10.1021/acs.jnatprod.1c00827
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and Molecular Docking Study of 3-Amino and 3-Hydroxy-seco A Derivatives of α-Amyrin and 3-Epilupeol as Inhibitors of COX-2 Activity and NF-kB Activation

Abstract: In this study, a series of novel 3-seco-A derivatives of the natural triterpenes α-amyrin (1) and 3-epilupeol (2) were synthesized by a one-pot radical scission−oxidation procedure and evaluated in vitro and in vivo for their capacity to inhibit the inflammatory process. For the in vitro studies, the trans-4-hydroxy-L-proline methyl ester derivatives (1f and 2f) were consistently effective in inhibiting NO, IL-6, and TNF-α secretion, as well as inhibition of NF-κB activation, in RAW cells stimulated by LPS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…NF-κB is a vital transcription factor that affects the expression of various inflammatory genes, such as IL-6 and TNF-α. 41 Our results revealed that LPS activated the NF-κB signaling pathway, thereby increasing IκB and p65 phosphorylation and IκB degradation. Previous studies have shown that LPS triggers inflammatory diseases by regulating the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…NF-κB is a vital transcription factor that affects the expression of various inflammatory genes, such as IL-6 and TNF-α. 41 Our results revealed that LPS activated the NF-κB signaling pathway, thereby increasing IκB and p65 phosphorylation and IκB degradation. Previous studies have shown that LPS triggers inflammatory diseases by regulating the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 52%
“…LPS activated the mRNA expression of IL‐6, IL‐8 and TNF‐α at all the indicated time points. NF‐κB is a vital transcription factor that affects the expression of various inflammatory genes, such as IL‐6 and TNF‐α 41 . Our results revealed that LPS activated the NF‐κB signaling pathway, thereby increasing IκB and p65 phosphorylation and IκB degradation.…”
Section: Discussionmentioning
confidence: 65%
“…Several typical binding modes of non-steroidal anti-inflammatory drugs (NSAIDs) interacting with COX-2 have been reported. These modes include the hydrophobic region of NSAIDs interacting with Tyr385, Trp387, and neighboring residues; the polar region of NSAIDs interacting with residues located above Tyr355; NSAIDs with negative charges interacting with Arg120 [47].…”
Section: Molecular Docking Analysis On Potential Cox-2 Inhibitorsmentioning
confidence: 99%